Relative muscle mass and the risk of incident type 2 diabetes: A cohort study - Hong, Sungwoo (PLoS One, 2017)
AIMS: The association between relative muscle mass (RMM) and incidence of type 2 diabetes (T2DM) is largely unknown. We examined whether RMM predicted development of T2DM in an apparently young healthy population. METHODS: This cohort study was comprised of 113,913 men and 89,854 women, free of T2DM at baseline, who underwent a health checkup examination and were followed-up annually or biennially for an average of 2.9 years. We used skeletal muscle mass index (SMI) as an indicator of RMM. SMI (%) [total skeletal muscle mass (kg)/body weight (kg)×100] was estimated using a bioelectrical impedance analyzer. The study outcome was incident T2DM, defined as fasting serum glucose ≥126 mg/dL, HbA1C ≥6.5%, or use of medication for T2DM. RESULTS: During 589,098.8 person-years of follow-up, 4,264 individuals developed T2DM (incidence rate, 7.2 per 1000 person-years). Median age (range) at baseline was 39.1 years (18.1–87.1). RMM was negatively associated with incidence of T2DM in a dose-response manner. The multivariate-adjusted hazard ratios (95% CIs) for incident T2DM comparing quartiles 3, 2 and 1 of RMM to the highest quartile were 1.32 (1.14–1.52), 1.63 (1.42–1.86), and 2.21 (1.94–2.51), respectively, for males and 1.18 (0.88–1.58), 1.46 (1.11–1.91), and 1.96 (01.51–2.53) for females (P for trend <0.001; 0.011). This association was stronger in younger or premenopausal subjects. CONCLUSIONS: RMM was negatively associated with development of T2DM in a large sample of young and middle-aged Korean adults. Further research is required to determine whether preservation of muscle mass through intervention affects the risk of T2DM.